Optimizing Diversion Policy Due to Overcrowding in Children's Special Development Institutions (LPKA) - Hamdi Hasibuan; Adi Mansar; Surya Perdana (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Child convicts are separated from adult convicts so that they are placed in the Special Children's Development Institution (LPKA), where this is a place for child convicts, not as a place to administer punishment as we know in Correctional Institutions (Lapas) which contain adult convicts. The essence of diversion with a restorative justice approach is the "transfer" of the process of resolving criminal acts from inside to outside the court through the method of consensus deliberation by prioritizing "restoration", "improvement" of the original situation before the crime occurred and by meeting the needs of victims, perpetrators and the community. This is stated in Article 8 of the SPPA Law that diversion is carried out through deliberation involving many parties. The results of diversion are expressed in the form of a "diversion agreement" which generally takes the form of peace (with or without compensation), handover to parents/guardians, education/training at educational institutions or LPKS; or community services. Negative impacts arising from the decline of prison and detention center residents include burdening staff, deterioration of living conditions, lack of access to education, training and employment, quality of health and physical and mental comfort which triggers tension and violence, increasing the risk of disease transmission. , also has an impact on state finances, human rights issues, health issues, security and economic issues due to illegal levies, security for officers, and the effectiveness of coaching. Therefore, it is important to have policies to mitigate the impacts arising from the overcrowding that occurs in prisons and detention centers